2014
DOI: 10.1038/srep06378
|View full text |Cite
|
Sign up to set email alerts
|

Optofluidic lens with tunable focal length and asphericity

Abstract: Adaptive micro-lenses enable the design of very compact optical systems with tunable imaging properties. Conventional adaptive micro-lenses suffer from substantial spherical aberration that compromises the optical performance of the system. Here, we introduce a novel concept of liquid micro-lenses with superior imaging performance that allows for simultaneous and independent tuning of both focal length and asphericity. This is achieved by varying both hydrostatic pressures and electric fields to control the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 29 publications
(30 reference statements)
1
77
0
2
Order By: Relevance
“…3(a), where, starting from the spherical meniscus at 0 V, the lens assumes aspherical profiles at higher voltages. These trends are consistent with the results reported by Mishra et al [2], where the LSA was shown to increase with the hydrostatic pressure for a spherical lens shape at zero voltage. Fig.…”
Section: Methodssupporting
confidence: 93%
See 4 more Smart Citations
“…3(a), where, starting from the spherical meniscus at 0 V, the lens assumes aspherical profiles at higher voltages. These trends are consistent with the results reported by Mishra et al [2], where the LSA was shown to increase with the hydrostatic pressure for a spherical lens shape at zero voltage. Fig.…”
Section: Methodssupporting
confidence: 93%
“…Figure 1(a) depicts the schematic of the experimental setup employed by Mishra et al [2]. The device consists of a top glass plate (light blue in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations